African NGO Collaborations And Networks As A Strategy For Resource Mobilization - Bagire, Vincent (Universiti Sains Malaysia, 2016)

(untitled)
NGOs re confirmed to be key actors in Africa’s developing economies as they address both social and economic aspects of life. There are cherished studies on their strategies and in regard to resource mobilization recent studies allude to declining donor resource envelop. An examination of the outcomes of different factors influencing NGOs in the context of developing countries provides fresh insights. Using the configuration theory, this study examined how Ugandan NGOs are using collaborations and networks to mobilize resources. Results showed that clusters of both tangible and intangible are critical in their operations. We propose a typology through which NGOs will continue to strengthen their collaborations and networks in view of their resource mobilization capabilities